A Nationwide Survey of UK Oncologists’ Views on the Choice of Radiotherapy Regime for the Reconstructed Chest Wall in Breast Cancer Patients - Nicola Davis; Rema Jyothirmayi (International Journal of Breast Cancer)
Aims. This paper describes a UK survey of the choice of radiotherapy regime for the reconstructed chest wall in breast cancer patients. Questions focused on which fractionation regime consultants choose, their reasons for this, whether the type of reconstruction influences their choice, and whether bolus is used in patients who have undergone immediate reconstructive surgery. Materials and Methods. Between July 2014 and July 2015 a survey was sent by email to UK consultant radiation oncologists treating breast cancer. Results. The response rate was 73%. 67% of respondents use 40 Gray (Gy) in 15 fractions, with 22% using 50 Gy in 25 fractions and 7% using other regimes. For 90% of consultants the type of reconstruction did not influence their decision regarding choice of fractionation. 83% of respondents do not usually use a bolus for chest wall radiotherapy in patients who have had immediate reconstructive surgery. Conclusions. This survey illustrates there is variation in practice in the management of patients with breast cancer who have undergone immediate reconstructive surgery in the UK. There is a need for further research to determine which fractionation regime is optimal, whether the type of surgery is relevant, and whether bolus should be added.